Retailtainment: Popota fun experience - Sousa, Filipa Inês da Graça (2013)
This project was developed in the context of master thesis, and it has the objective to develop a strategic marketing plan. In this respect, and applying the knowledge acquired over the last four years, it is developed the “Popota Fun Experience”, a retail toys store of a well-known character by Portuguese population. Popota Fun Experience is a retail store target to children and it is based in two important concepts: entertainment and education. Having said that, the main objective is to educate children while they are playing. It is a new retail store concept with a different positioning from the main competitors and that will stimulate the market growth. In order to support the opening of Popota Store, it is defined a marketing strategy and it is designed the retailing-mix variables.